Addressing Large Movements of Refugees and Migrants - Kim, Jim Yong (World Bank, Washington, DC, 2018)
Jim Yong Kim, President of the World Bank Group, stated that the World Bank Group is approaching the issue in four new ways. First, the Bank is responding to the realization that we need much better data and analysis about refugees, migrants, and internally displaced people. Second, with partners, the Bank is developing warning systems to anticipate where people will be moving. Third, the Bank is working during crises to help host countries improve the business climate and use the private sector as a driver to stimulate economic growth. Finally, the Bank is looking for longer-term solutions in many countries, including Afghanistan, Kenya, and Somalia, on issues ranging from increasing agricultural productivity in areas hosting refugees to helping refugees return to their countries. He urged a strengthen engagement with the United Nations, other multilateral development banks, the private sector, and civil society to address the needs of so many millions of displaced people.